Evolution of collective and noncollective structures in Xe 123 - Basu, A.; Singh, A.K.; Nag, S.; Hagemann, G.B.; Sletten, G.; Herskind, B.; Wilson, A.N.; Rogers, J.; Ragnarsson, I.; Hübel, H.; Chmel, S.; Janssens, R.V.F.; et al. (American Physical Society, 2020)
An experiment involving a heavy-ion-induced fusion-evaporation reaction was carried out where high-spin states of Xe123 were populated in the Se80(Ca48,5n)Xe123 reaction at 207 MeV beam energy. Gamma-ray coincidence events were recorded with the Gammasphere Ge detector array. The previously known level scheme was confirmed and enhanced with the addition of five new band structures and several interband transitions. Cranked Nilsson-Strutinsky (CNS) calculations were performed and compared with the experimental results in order to assign configurations to the bands. © 2020 American Physical Society. US UK.